Stimuli-Responsive Proteinosomes Based on Biohybrid Shell Cross-Linked Micelles - Zhang, Lixin (Langmuir : the ACS journal of surfaces and colloids, 2021)
A new method of stimuli-responsive proteinosome fabrication with the shell cross-linked micelle as a template is reported in this research. A thermoresponsive diblock copolymer poly[di(ethylene glycol) methyl ether methacrylate]-b-poly[poly(ethylene glycol) methyl ether methacrylate-co-pyridyl disulfide methacrylamide] [PDEGMA-b-P(PEGMA-co-PDSMA)] was synthesized and self-assembled into micelles with PDEGMA cores and P(PEGMA-co-PDSMA) shells at the temperature above its lower critical solution temperature (LCST). Reduced bovine serum albumin (BSA) molecules with six thiol groups were used to cross-link the shells of the micelles by reacting with the pendant pyridyl disulfide groups on the P(PEGMA-co-PDSMA) block. At a temperature below the LCST of the polymer, the PDEGMA cores were dissolved in water, affording proteinosomes with a size of about 50 nm and capsule-like structures. The proteinosome was also thermoresponsive with a phase transition temperature at 35 °C. The fabrication of the proteinosome had no obvious influence on the structure and activity of BSA, and BSA retained most of its secondary structure and esterase-like activity. Because the BSA molecules were connected to the polymer chains through disulfide bonds, they could be released upon addition of dithiothreitol. The in vitro cell viability evaluation and the cellular uptake assay demonstrated that the proteinosome showed low toxicity to NIH 3T3 and 4T1 cells and could be internalized into the 4T1 cells